2009
DOI: 10.3746/jkfn.2009.38.12.1740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol on Wine Sensory Evaluation Preference Analysis

Abstract: In this study, effect of resveratrol concentration on wine taste was investigated. Content of resveratrol in 14 different wines were quantified using HPLC. The resveratrol concentrations in the Australian wine samples (grape species: Syrah) with 3 vintage years were analyzed and different concentrations of resveratrol were observed (2.89~3.84 mg/L). Variation in wine grape species with the same wine manufacturer (Chile, 2006) and variation in different manufacturing country of origin with same wine grape spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The concentration of oxyresveratrol and resveratrol in 50% ethanol extract of Smilax china root was 31.03 and 120.48 µg mL −1 , respectively, indicating that concentration of resveratrol was 3.88 times higher than that of oxyresveratrol. A previous study found that the amount of resveratrol in red wine ranged from 0.2 to 5.8 mg L −1 . Our results indicate the concentration of resveratrol in Smilax china root is about 20‐ to 600‐fold higher than that in red wine, implying that Smilax china extract could be developed as a high‐value added plant.…”
Section: Resultsmentioning
confidence: 55%
“…The concentration of oxyresveratrol and resveratrol in 50% ethanol extract of Smilax china root was 31.03 and 120.48 µg mL −1 , respectively, indicating that concentration of resveratrol was 3.88 times higher than that of oxyresveratrol. A previous study found that the amount of resveratrol in red wine ranged from 0.2 to 5.8 mg L −1 . Our results indicate the concentration of resveratrol in Smilax china root is about 20‐ to 600‐fold higher than that in red wine, implying that Smilax china extract could be developed as a high‐value added plant.…”
Section: Resultsmentioning
confidence: 55%